Deficient Explicit Access to Phonological Representations Explains Phonological Fluency Difficulties in Greek Children With Dyslexia and/or Developmental Language Disorder - Mengisidou, Maria; Marshall, Chloë R. (Frontiers in Psychology, 2019)
It is well-established that children with dyslexia and/or Developmental Language Disorder (hereafter children with DDLD) perform poorly on phonological tasks compared to typically-developing (TD) children. However, there has been some debate as to whether their phonological deficit arises directly from an impairment in phonological representations, or instead from deficient access to (intact) phonological representations. This study tested the Degraded Phonological Representations Hypothesis and the Deficient Phonological Access Hypothesis using a task that is not often used with children with DDLD, namely phonological fluency. Both hypotheses predict that children with DDLD will retrieve fewer items than TD peers in the phonological fluency task. However, while the Degraded Phonological Representations Hypothesis predicts smaller clusters of phonologically-related items in children with DDLD, the Deficient Phonological Access Hypothesis predicts that the two groups will not differ in cluster size. How phonological fluency performance related to children’s language, literacy and phonological skills was investigated. Further, the specificity of a phonological fluency deficit in children with DDLD was tested using a nonverbal (design) fluency task. Sixty-six children with DDLD aged 7-12 years and 83 TD children aged 6-12 years, all monolingual Greek speakers, were tested on three phonological fluency categories, on nonverbal IQ, language, literacy and phonological tasks, and on a design fluency task. The DDLD group produced significantly fewer correct responses and fewer switches compared to the TD group, but the two groups showed similar clustering and average cluster size. After controlling for age, children’s language, literacy and phonological skills significantly predicted the number of correct responses produced. The two groups did not differ significantly on the number of unique designs generated in the design fluency task. Furthermore, children with DDLD showed poorer phonological fluency performance relative to their TD peers even after design fluency performance was controlled, demonstrating the specificity of their phonological fluency deficit. This study adds to the theoretical debate on the locus of the phonological deficit in dyslexia and DLD. The findings support the hypothesis that the phonological deficit in dyslexia and DLD lies in deficient explicit access to intact phonological representations.